Preliminary data suggestive of a novel translational approach to mesothelioma treatment: imatinib mesylate with gemcitabine or pemetrexed. Issue 8 (20th February 2007) - Bertino, Pietro; Porta, Camillo; Barbone, Dario; Germano, Serena; Busacca, Sara; Pinato, Sabrina; Tassi, Giancarlo; Favoni, Roberto; Gaudino, Giovanni; Mutti, Luciano
Abstract : Background: Malignant mesothelioma is a cancer which is refractory to current treatments. Imatinib mesylate is a selective inhibitor of tyrosine kinases such as bcr-abl, c-Kit, c-Fms and platelet derived growth factor receptor β (PDGFRβ). PDGFRβ is often overexpressed in mesothelioma cells and is a therapeutic target for imatinib in some solid tumours. A study was undertaken to assess whether imatinib alone or combined with chemotherapeutic agents may be effective for treating mesothelioma. Methods: Cultures from mesothelioma MMP, REN and ISTMES2 cell lines were treated with imatinib alone or in combination with a chemotherapeutic agent. Results: Imatinib induced cytotoxicity and apoptosis selectively on PDGFRβ positive mesothelioma cells via blockade of receptor phosphorylation and interference with the Akt pathway. Of the chemotherapeutic agents tested in combination with imatinib, a synergistic effect was obtained with gemcitabine and pemetrexed. Conclusions: This study provides a rationale for a novel translational approach to the treatment of mesothelioma which relies on enhancement of tumour chemosensitivity by inhibition of Akt.